Definition, signs and types of administrative and procedural guarantees: Established views and the need for their modernization - Shapoval, Roman Volodymyrovych; Kolomoiets , Tetiana Olexsandrivna; Valeriivna Brusakova, Oksana; oglu Garayev, Mikayil Vagif (DIXI, 2021)
The purpose of this article is to determine the nature and content of administrative and procedural guarantees. In this regard, it is necessary to solve the following tasks: To clarify the definition of administrative and procedural guarantees, to characterize their types, to reveal the features of administrative and procedural guarantees, and to determine the place of this legal phenomenon in the general legal system. Issues related to theoretical and legal interpretation, legislative definition and direct implementation of administrative and procedural guarantees are updated and considered. The influence of administrative-procedural guarantees on the level of development of the domestic legal system is analyzed. Attention is drawn to the fact that the quality of proper functioning of administrative-procedural guarantees directly depends on the development of state institutions of a particular country, as well as on the level of perfection and efficiency of the entire state-power mechanism, i.e. the state system. Given that the essence of modern administrative and procedural guarantees provides for the proper consolidation of rights, freedoms and legitimate interests of individuals, it is justified that the key role in these processes will always play the level of legal awareness, along with the level of transparency and timeliness. The author’s definitions of the terms “administrative-procedural guarantees”, “protection of legal guarantees of citizens” and “legal awareness of the population” are given. Some of the characteristic features of foreign models of administrative and legal regulation are proposed for implementation.
Keywords: administrative process; legal awareness; legal regulation administrative law; protection of legitimate interests; protection of rights and freedoms of persons; administrative-procedural guarantees